Technology Innovation in Underground Construction - Beer, Gernot (CRC Press, 2009)
"This richly-illustrated reference guide presents innovative techniques focused on reducing time, cost and risk in the construction and maintenance of underground facilities:A primary focusof the technological development in underground engineering is to ease the practical execution and to reduce time, cost and risk in the construction and maintenance of underground facilities such as tunnels and caverns. This can be realized by new design tools for designers, by instant data access for engineers, by virtual prototyping and training for manufacturers, and by robotic devices for maintenance and repair for operators and many more advances. This volume presents the latest technological innovations in underground design, construction, and operation, and comprehensively discusses developments in ground improvement, simulation, process integration, safety, monitoring, environmental impact, equipment, boring and cutting, personnel training, materials, robotics and more. Thesenew features are the result of a big research project on underground engineering, which has involved many players in the discipline. Written in an accessible style and with a focus on applied engineering, this book is aimed at a readership of engineers, consultants, contractors, operators, researchers, manufacturers, suppliers and clients in the underground engineering business. It may moreover be used as educational material for advanced courses in tunnelling and underground construction."--Provided by publisher.